Choosing from the ‘menu of manipulation’: evidence from Ghana - Lynge-Mangueira, H (2018)
This thesis explores the patterns of electoral manipulation in Ghana. Inspired by Andreas Schedler's essay, The Menu of Manipulation, in which he provides a "list of electoral sins" (Schedler 2002, 45), the thesis asks the following research question: how do African politicians choose from the menu of manipulation? To answer this question, the thesis develops a theory about the costs and benefits of electoral manipulation. The theory is based on three arguments: first, that in addition to the direct benefits of electoral manipulation, meaning the increased chance of winning, there are important indirect benefits that drive some politicians to rig, even when victory is guaranteed or entirely beyond reach; second, that electoral manipulation is expensive and that the direct costs, meaning what politicians spend, discourage them as much as the indirect costs, i.e. the risk of getting caught; and, third, that different types of electoral manipulation have different cost-benefit profiles, allowing politicians to tailor their rigging strategies. The thesis tests this theory against original data from Ghana. First, drawing on a dataset, containing information about every, regular, constituency-level parliamentary election over the 2008 and 2012 electoral cycles, it shows that different types of electoral manipulation have different patterns, caused by their different cost-benefit profiles; that not all types are driven by electoral uncertainty; and that there are trade-offs between the direct and indirect costs of rigging. Second, drawing on participant observations from two parliamentary constituencies in eastern Ghana, the thesis shows that consider both their electoral prospects and clientelistic networks, when they choose between different types of electoral manipulation, and that they revert to riskier types only as a last resort: when there are no other options available on the menu of manipulation. The thesis contributes to the academic literature in two ways. First, it adds to the growing body of work pointing to the direct costs and the indirect benefits of electoral manipulation. Second, it proposes a framework for approximating the properties of different types of electoral manipulation and making predictions about their patterns.